THE PAPAR TRADITION IN THE CUSTOM ON DEATH IN TEUPAH TENGAH SUBDISTRICT, SIMEULUE REGENCY - Sri Rahayu Nengsih Ainun; Aslam Nur (The Department of Islamic History and Culture in cooperation with the Center for Research and Community Service, Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2021)
This article is entitled